Barriers to green supply chain implementation in the electronics industry - S. Khiewnavawongsa (2018)
© 2013 IEEE. This study identifies barriers to green supply chain management implementation in the electronics industry. The study explores factors that prevent companies from implementing green projects, and identifies green implementation types that the electronics industry has adopted. Data was gathered by interview and survey methods, which participants represented manufacturers and distributors in the US electronics industry. Survey questions included 33 barriers to green implementation, and readiness to green implementation using six implementation types. Data was analyzed by SPSS. Results showed that the financial impact is the major factor for green implementation by electronics companies. Company size did not impact green supply chain barriers. However, small-sized companies were less ready to implement green initiatives for most projects. Generally, distributors were more affected from barriers to green implementation than manufacturers. Electronics companies were most ready to implement with green manufacturing and packaging projects while green suppliers projects were least ready for implementation.